Effect of plasma power on reduction of printable graphene oxide thin films on flexible substrates. (18th May 2018) - Banerjee, Indrani; Mahapatra, Santosh K; Pal, Chandana; Sharma, Ashwani K; Ray, Asim K
Abstract: Room temperature hydrogen plasma treatment on solution processed 300 nm graphene oxide (GO) films on flexible indium tin oxide (ITO) coated polyethylene terephthalate (PET) substrates has been performed by varying the plasma power between 20 W and 60 W at a constant exposure time of 30 min with a view to examining the effect of plasma power on reduction of GO. X-ray powder diffraction (XRD) and Raman spectroscopic studies show that high energy hydrogen species generated in the plasma assist fast exfoliation of the oxygenated functional groups present in the GO samples. Significant decrease in the optical band gap is observed from 4.1 eV for untreated samples to 0.5 eV for 60 W plasma treated samples. The conductivity of the films treated with 60 W plasma power is estimated to be six orders of magnitude greater than untreated GO films and this enhancement of conductivity on plasma reduction has been interpreted in terms of UV-visible absorption spectra and density functional based first principle computational calculations. Plasma reduction of GO/ITO/PET structures can be used for efficiently tuning the electrical and optical properties of reduced graphene oxide (rGO) for flexible electronics applications.